Playing exposure does not affect movement characteristics or physiological responses of elite youth footballers during an intensified period of competition - Gibson, N. V.; McCunn, R.; MacNay, S. A.; Mullen, T.; Twist, C. (Science and Medicine in Football, 2018)
Objective: Investigate the effect of playing time on physiological and perceptual responses to six, 60 min matches played over five days. Methods: Thirty youth footballers (age = 14.1 ± 0.4 years; body mass = 57.4 ± 12.9 kg; stature 169.3 ± 7.7 cm) were grouped into low (<250 min; LPG, n = 18) and high (=250 min; HPG, n = 12) match exposure groups and monitored daily for lower body power and perceived wellness. Match running demands were assessed using GPS technology in total distance (m/min), low (<13 km/h) and high (=13 km/h) speed categories. Data were analysed using hypothesis based testing and effect sizes (ES). Results: HPG performed moderately more total distance (103.7 ± 10.4 cf. 90.2 ± 19.7 m/min, P = 0.03; ES = 0.74 ± 0.63) and high-speed running (26.7 ± 6.6 cf. 20.3 ± 6.5 m/min, P = 0.01; ES = 0.87 ± 0.6) than LPG across all matches. Differences of a small magnitude were observed for lower body power (P = 0.08; ES = 0.59 ± 0.8) and perceived wellness (P = 0.09; ES = 0.42 ± 0.4) which were both higher in the HPG. Conclusions: Youth footballers appear well equipped to deal with intensified periods of competition, irrespective of match exposure.